1982
DOI: 10.1007/bf00044473
|View full text |Cite
|
Sign up to set email alerts
|

Lake Vechten: aspects of its morphometry, climate, hydrology and physico-chemical characteristics

Abstract: The physiography of Lake Vechten (The Netherlands) is described together with morphometric data . The lake (surface area 4 .7 ha ; mean depth 6 .0 m) consists of two basins with maximum depths of 10 .5 and 11 .9 m . Meteorological conditions in the region and horizontal groundwater flow play an important role in the renewal time, which is about two years . The lake has in most years a circulation period from November till April but in some years, when the ice cover is prolonged, it is stratified in winter as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…The low DI-TP concentrations for both lakes (Fig. 5) reflect the fact that these lakes are mainly fed by precipitation and by nutrient-poor groundwater (Hordijk, 1993;Steenbergen & Verdouw, 1982;van Donk, 1983) and are not influenced by river activity. Lake Plas Vechten is an isolated seepage lake with neither an outlet nor an inlet.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The low DI-TP concentrations for both lakes (Fig. 5) reflect the fact that these lakes are mainly fed by precipitation and by nutrient-poor groundwater (Hordijk, 1993;Steenbergen & Verdouw, 1982;van Donk, 1983) and are not influenced by river activity. Lake Plas Vechten is an isolated seepage lake with neither an outlet nor an inlet.…”
Section: Discussionmentioning
confidence: 97%
“…Best (1982) described a decline in macrophytes in Lake Plas Vechten in the period of 1963 to 1980 and also showed that in the summer periods from 1978 onwards the lake's catchment was used as farm land, fertilized by artificial fertilizer and cattle manure. Steenbergen and Verdouw (1982) concluded that phosphorus release from the sediments and turbulent eddy flows play a significant role for the transport of nutrients from the hypo-to the epilimnion in this lake. After 1980, when nutrient input increased and consequently led to enhanced primary production, this may have played a significant role in accelerating eutrophication in Lake Plas Vechten.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The mean K, for the entire water column and secchi disc readings for Keyhole Lake are similar to late July values for Lake Schrader, Alaska ( Kd=0.59 and secchi disc=4 m, Hobbie, 1962) and to coefficients of some European north temperate lakes (e.g., Lake Esthwaite, Kd=0.59 and secchi disc=3.7 m, Macan, 1970;Lake Hampen, K,=0.60 and secchi disc=3.7 m, Sand-Jensen and Ssndergaard, 1981;Lake Vechten, Kd=0.60 and secchi disc=3.5 m, Steenberger and Verdouw, 1982). Lake Schrader is an oligotrophic lake (summer chlorophyll a=0.98 mgm-3, while Lakes Esthwaite, Hampen and Vechten are mesotrophic (summer chlorophyll a > 2 mgm3).…”
Section: Discussionmentioning
confidence: 99%